Effect of boron sources in the thermal behavior of a clay-based ceramics - Hernández, Maria Florencia (2022)
Boron oxide sources as fluxing agents for clay-based materials have been a problem for the high solubility of these additives, however the dry milling-mixing-granulating route for clay based ceramics has been proposed and implemented with noticeable energetic advances. In the present study, the role of different boron oxide sources in the thermal behavior and sinterability of ceramic materials based on kaolinite clay was evaluated. Four boron sources were evaluated: Boric acid, borax, colemanite and ulexite. Four binary mixtures were made in a planetary mill to obtain uniform mixtures. For systematic comparison, the boron content added in all samples was 1 wt%. The thermal behavior evaluation of the mixtures was carried out by a multi-technique approach accompanied by textural, microstructural characterization complemented by a deep crystalline and non-crystalline phase evolution. Ulexite and borax presented the highest fluxing effect and colemanite has an even more moderate effect than boric acid. The observed microstructure was similar to other clay-based ceramics, with quartz grains, cristobalite and mullite embedded in the silica-based vitreous phase. The present study provides information for the additional design of clay-based materials with boron oxides as fluxing agents. The dry route alternative for using these agents was effective.